The inverted U-shaped impact of the digital economy on indirect household carbon emissions — an empirical study based on CFPS - Chen, Ying; Chen, Donglin; Gao, Chenfeng; Wei, Xiaochao (Frontiers in Environmental Science, 2025)
IntroductionIn the era of the booming digital economy and global efforts to reduce carbon emissions, this study investigates how digital economy growth impacts indirect household carbon emissions (IHCEs). Understanding this relationship is critical, as the digital economy has the potential to both drive and mitigate carbon emissions, depending on its stage of development and regional context.MethodsUsing panel data from the 2014–2018 China Family Panel Studies (CFPS), a fixed effects model is applied to analyze the relationship between digital economy growth and IHCEs. The study examines regional variations, levels of digital economy development, and consumption categories to identify heterogeneous effects.ResultsThe findings reveal an inverted U-shaped relationship between the digital economy and IHCEs. Initially, IHCEs rise due to increased consumption of energy-intensive products, but as digital technologies mature, emissions decline due to improved efficiency and sustainable consumption. Heterogeneity analysis shows that the inverted U-shaped relationship is more pronounced in less developed digital economy regions, while in advanced regions, the relationship is less significant. Regionally, the eastern region, with its advanced infrastructure and green technologies, effectively curbs IHCEs, whereas the central region experiences increased emissions, and the western region exhibits the inverted U-shaped pattern. In terms of consumption, the digital economy significantly impacts housing and food-related emissions, while other categories show mixed or minor effects.DiscussionThese findings highlight the dual role of the digital economy in both driving and mitigating carbon emissions. Policymakers should adopt region-specific strategies, invest in digital infrastructure, and promote sustainable consumption practices to leverage the digital economy for carbon reduction. The study underscores the importance of managing expectations and addressing discrepancies between digital economy growth and its environmental impacts, offering valuable insights for achieving sustainable development goals.